PENGGUNAAN RIPPLE DOWN RULE UNTUK MENDIAGNOSIS PENYAKIT ANAK - Daniel Hutama Putra; Joko Purwadi; Antonius Rachmat Chrismanto (Universitas Kristen Duta Wacana, 2014)
This research is implementing Ripple Down Rule method to diagnosing pediatric diseases. Ripple Down Rule is a method based on tree which formed a representation of expert knowledge. This method is much easier to use and improved knowledge by adding, deleting, and changing the established tree. Research carried out shows that Ripple Down Rule method can be used to diagnose pediatric diseases. Results show that this system is having increase in accuracy of first test to the second test, after the change of knowledge using the Ripple Down Rule.